DEVELOPMENT OF BASIC COMPETENCY JOBSHEET TO CUT A RECTANGULAR THREAD USING A LATHE FOR VOCATIONAL SENIOR HIGH SCHOOL - Zuhda Bahtiar, fahmy; Khumaedi, M.; Syamwil, Rodia (Journal of Vocational and Career Education, 2019)
This study implemented the use of basic competency job-sheet to lathe for a rectangular thread for students of vocational high school. The numerous numbers of students who asked questions indicated that learning has been ineffective. Pretest results proved that the competency in the use of lathe with a rectangular thread did not meet KKM value. This study’s objective therefore was to understand validity, reliability, effectiveness and practicality of the jobsheet for vocational senior high school students.This study used a Research and Development method with 4Da study model approach comprising of Define, Design, Develop, and Disseminate. However, this study  only used 3D, specifically, Define, Design and Develop. The Kappa Coefficient of the VCR raw material was used to gain validity and reliability of the jobsheet content. Two group pretest-posttest designs were used to test effectiveness of the jobsheet, and students’ response to questionnaires were used to understand their  responses.The results of study indicate that validity of the jobsheet content is derived from 2 raters which indicate CVI value with a valid category. Reliability of the jobsheet content showed this was the most substantial category. The results of effectiveness given illustrates that the increasing mean of the posttest values where found effective, while that of students’ responses given to an experimental class was in the very feasible category. The conclusion of this study therefore is valid, reliable, effective and practical development and can be usable for practice learning to lathe the rectangular thread.